Determinants of debt-equity choice on family companies - evidence from Malaysia / Muhammad Hishamuddin Kamaronzaman - Kamaronzaman, Muhammad Hishamuddin (2017)
The aim of this paper is to analyse the determinants of capital structure of family companies in Malaysia. To study the capital structure family company, lot of previous study was being reference in this study. Theories that were used in this study are trade-off theory and pecking order theory. This study focus used three independent variables well-suited with the up-to-date achievements in the field today. For the dependent variable, this study used leverage. The result shows positive relationship between size and tangibility toward leverage. However, profitability shows the opposite result. This study used 119 companies that fulfilled with criteria as family business.